Development and validation of a finite element model to simulate the opening of a medial opening wedge high tibial osteotomy. Issue 4 (12th March 2019) - Carranza, Victor A.; Reeves, Jacob; Getgood, Alan; Burkhart, Timothy A.
Abstract: Medial opening wedge high tibial osteotomy (MOWHTO) is a surgical procedure intended to alter the coronal and sagittal plane alignment of the lower limb to primarily relieve the symptoms of osteoarthritis in the medial compartment of the knee. The purpose of this work was to develop and validate a finite element model to simulate the opening of a high tibial osteotomy and determine whether a pilot hole at the cortical hinge reduces the risk of lateral cortical fracture. Fifteen models were reconstructed from CT images of eight cadaveric specimens. The validated models indicated that the addition of the pilot hole increased the stresses and likelihood of a type-I and type-II fractures during the opening of a medial open wedge high tibial osteotomy compared to the no-hole condition.